2014
DOI: 10.1111/cobi.12349
|View full text |Cite
|
Sign up to set email alerts
|

Pollution, habitat loss, fishing, and climate change as critical threats to penguins

Abstract: Palabras Clave: captura accesoria, competencia por recursos, contaminación marina, degradación de hábitat, sobrepesca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(154 citation statements)
references
References 58 publications
(73 reference statements)
3
144
1
Order By: Relevance
“…For example, tracking data has revealed that blue whales (Balaenoptera musculus) have limited ability to avoid collisions with ships [63] and that small shifts in traffic routes could reduce the risk of ship-strike [64]. The description of movement patterns in situations and at times when marine megafauna are exposed to potential threats from anthropogenic activities must be a key goal for research that seeks to optimise strategies for the management, conservation and resilience of this fauna [48,65].…”
Section: How Do Anthropogenic Activities (Eg Shipping Fishing Watmentioning
confidence: 99%
“…For example, tracking data has revealed that blue whales (Balaenoptera musculus) have limited ability to avoid collisions with ships [63] and that small shifts in traffic routes could reduce the risk of ship-strike [64]. The description of movement patterns in situations and at times when marine megafauna are exposed to potential threats from anthropogenic activities must be a key goal for research that seeks to optimise strategies for the management, conservation and resilience of this fauna [48,65].…”
Section: How Do Anthropogenic Activities (Eg Shipping Fishing Watmentioning
confidence: 99%
“…SRP are currently classified as Vulnerable to extinction (BirdLife International 2017) due to substantial population declines in recent decades over its entire range. These have been linked to several factors such as habitat degradation, chemical pollution, and algal blooms, among others (see review in Pütz et al 2013;Trathan et al 2014). In the Southwest Atlantic, there are two main assemblages: Staten Island (ca.…”
Section: Introductionmentioning
confidence: 99%
“…However, given limited available conservation resources, some comparison gives context and aids prioritisation. Climate change is likely to affect all of these species, albeit in different ways (García-Borboroglu & Boersma 2013, Trathan et al 2015, Mattern et al 2017. In order to improve resilience of penguin populations in the face of climate change, other threats need to be substantially reduced, and incidental mortality in fishing gear is one threat that can be addressed immediately.…”
Section: Importance Of Bycatch Compared To Other Threats For the Mostmentioning
confidence: 99%
“…comm.). AlfaroShigueto et al (2010) noted that mortality of Humboldt penguins could be exacerbated by the retention of incidentally captured penguins for human consumption, and Trathan et al (2015) mentioned egg collection as a threat. As this review has documented, Humboldt penguins are bycaught in gillnets (Majluf et al 2002, Pro Delphinus unpubl.…”
Section: Importance Of Bycatch Compared To Other Threats For the Mostmentioning
confidence: 99%
See 1 more Smart Citation